PERAN MAJAS SARKASME DAN NILAI PENDIDIKAN KARAKTER DALAM PUISI MENCARI TANAH LAPANG KARYA WIJI THUKUL DAN RELEVANSINYA DENGAN PENGAJARAN SASTRA DI PERGURUAN TINGGI - Andromeda Nova Hartavi; Sarwiji Suwandi; Sri Hastuti (Universitas Sebelas Maret, 2019)
This research aims to describe and explain the role of sarcasm, the value of character education in the collection of poetry Mencari Tanah Lapang by Wiji Thukul, and the relevance the role of sarcasm and the value of character education in the collection of poetry Mencari Tanah Lapang by Wiji Thukul on the teaching of literature in universities. Technique of subject sampling is purposive sampling. Data collection techniques used are document analysis and interviews. The validity of data in this study is done by using critical discourse analysis techniques. The results of this research are: (1) there are 62 sarcasm in the collection of poetry Mencari Tanah Lapang that serve as satirical of rules, satire of politics, satire of development, satire of education, satire of social inequality, and satire world health; (2) the value of character education contained in the collection of poetry Mencari Tanah Lapang is religious values, honesty, tolerance, hard work, democracy, reading, and social care;(3) the role of sarcasm majors and the value of character education contained in the collection of poetry Mencari Tanah Lapang can be used as a literary teaching material with the subject of poetry in the study program of Indonesian literature.